2007
DOI: 10.1016/j.aim.2006.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Geometric representation theory for unitary groups of operator algebras

Abstract: Geometric realizations for the restrictions of GNS representations to unitary groups of C * -algebras are constructed. These geometric realizations use an appropriate concept of reproducing kernels on vector bundles. To build such realizations in spaces of holomorphic sections, a class of complex coadjoint orbits of the corresponding real Banach-Lie groups is described and some homogeneous holomorphic Hermitian vector bundles that are naturally associated with the coadjoint orbits are constructed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 34 publications
0
34
0
1
Order By: Relevance
“…j / H K on spanfK W 2 Dg whose completion gives rise to a Hilbert space denoted by H K , which consists of sections of the bundle …; see [8,Th. 4.2].…”
Section: Linear Connections For Reproducing Kernelsmentioning
confidence: 99%
See 1 more Smart Citation
“…j / H K on spanfK W 2 Dg whose completion gives rise to a Hilbert space denoted by H K , which consists of sections of the bundle …; see [8,Th. 4.2].…”
Section: Linear Connections For Reproducing Kernelsmentioning
confidence: 99%
“…Recently, reproducing kernels on vector fiber bundles (which are a clear geometric object) has revealed fruitful in representation theory and function theory [11,20,33] and to construct Borel-Weil-type (infinite-dimensional) realizations of GNS representations as well as Stinespring dilations [3,8]. In the present article, the attention is focused on the specific differential geometry aspects of such a relationship.…”
Section: Introductionmentioning
confidence: 99%
“…Using a charaterization (and labelling) of invariant complex structures on infinite-dimensional homogeneous manifolds (Theorem 6.1 in [4]), we prove in Section 3 below that U A /U A (p) and G A /G A ([p]) are locally biholomorphic complex manifolds. Moreover, it is also shown that G A /G A (p) is a complexification of U A /U A (p), and then these results are translated in terms of homogeneous vector bundles, in the spirit of Theorem 5.8 in [5]. (A complementary perspective on these manifolds can be found in [6].)…”
Section: Introductionmentioning
confidence: 95%
“…This point is particularly important for the applications to the adjoint or coadjoint orbits that show up in connection with the operator algebras (see [9,12,13,19] and Corollary 16). Indeed, the unitary groups of C * -algebras are in general nonconnected (although they are connected in the special case of W * -algebras), while nothing seems to be known on connectedness of the unitary groups associated with general non-separable operator ideals (compare Remark 4.9 in [9]).…”
Section: Introductionmentioning
confidence: 97%